2016
DOI: 10.1039/c6dt00876c
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo-icosahedral cage {Gd12} based on aminomethylphosphonate

Abstract: Reaction of (aminomethyl)phosphonic acid (ampH2) with a mixture of gadolinium and cobalt pivalates under solvothermal conditions, led to a pseudo-icosahedral cage {Gd12}, which shows a large magnetocaloric effect (MCE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Three different amino-phosphonate binding modes are found in the compounds. Previous results from our group and others indicate that the alkyl groups attached to the aminophosphonic acid has a strong effect on the structures and properties of the lanthanide(III) phosphonates isolated [38,39]. The aminophosphonic acids, H 2 NRPO 3 H 2 (R = alkyl or aryl group), have been proved to be very useful ligands for the synthesis of metal phosphonates with new structure types in which the organic part plays a controllable spacer role and the two inorganic-PO 3 groups chelate with metal ions to form one-, two-, and three-dimensional structures [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Three different amino-phosphonate binding modes are found in the compounds. Previous results from our group and others indicate that the alkyl groups attached to the aminophosphonic acid has a strong effect on the structures and properties of the lanthanide(III) phosphonates isolated [38,39]. The aminophosphonic acids, H 2 NRPO 3 H 2 (R = alkyl or aryl group), have been proved to be very useful ligands for the synthesis of metal phosphonates with new structure types in which the organic part plays a controllable spacer role and the two inorganic-PO 3 groups chelate with metal ions to form one-, two-, and three-dimensional structures [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the phosphonate moiety is an efficient functional group for the construction of molecular cages [38,39]. Winpenny and co-workers reported results using t-butylphosphonic acid (H 2 3 ] + cation, the anion of the compound contains nine Ln(III) metal ions in a ring and a tenth Ln(III) metal ion at the center of the structure, the ten metal sites are almost co-planar.…”
Section: Syntheses Of the Complexesmentioning
confidence: 97%
See 3 more Smart Citations